Pengaruh Tandem Walking Exercise dan Ankle Strategy Exercise terhadap Risiko Jatuh pada Lansia di Jatiyoso - Binti Kholifatu Rohmah; Young Ari Kusworo; Azizah Rahmawati; Fiqi Widyawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The aging process leads to a decline in body functions, particularly muscle strength, balance, and postural control. These physiological changes increase the susceptibility of older adults to falls, which may result in injuries, reduced functional capacity, and decreased independence in performing activities of daily living (ADL). This study aimed to evaluate the effects of Tandem Walking Exercise (TWE) and Ankle Strategy Exercise (ASE) on reducing fall risk and to compare the effectiveness of both interventions among older adults in Jatiyoso. This study employed a quasi-experimental method using a two-group pretest-posttest design. A total of 30 older adults were recruited through purposive sampling and allocated into two intervention groups: the TWE group (n = 15) and the ASE group (n = 15). Both groups received 12 exercise sessions over four weeks, with a frequency of three sessions per week. Fall risk was assessed using the Timed Up and Go Test (TUGT). Data were analyzed using the Wilcoxon Signed Rank Test and the Mann-Whitney U Test. The results showed that both Tandem Walking Exercise and Ankle Strategy Exercise significantly reduced fall risk among older adults (p < 0.001 and p = 0.001, respectively). Furthermore, the between-group analysis revealed a significant difference in effectiveness (p = 0.004), with the Tandem Walking Exercise group demonstrating a greater reduction in fall risk than the Ankle Strategy Exercise group. These findings suggest that Tandem Walking Exercise may be considered a more effective intervention for reducing fall risk among older adults.